The THE EFFECT OF PROFITABILITY AND SOLVENCY ON FIRM VALUE IN ISLAMIC BANKS IN INDONESIA - Halfiah Rustamin; Syahriyah Semaun; Damirah Damirah; Muliati Muliati; Andi Ayu Frihatni (Economos : Jurnal Ekonomi dan Bisnis, 2026)
Abstract This study aims to analyze the effect of profitability and solvency on firm value in Islamic banks in Indonesia. Firm value reflects investors’ perceptions of a company’s performance and future prospects, making it an important indicator in investment decision-making. This study employs a quantitative approach using secondary data obtained from the financial statements of Islamic banks in Indonesia. Multiple linear regression analysis is applied to examine the effect of profitability and solvency, both partially and simultaneously, on firm value. The results show that profitability has a significant effect on firm value, indicating that the ability of Islamic banks to generate profits plays an important role in increasing investor confidence. Meanwhile, solvency also has a significant effect on firm value, suggesting that the banks’ ability to meet their financial obligations is a key consideration in firm valuation. Simultaneously, profitability and solvency have a significant effect on firm value in Islamic banks in Indonesia. These findings are expected to contribute to the development of Islamic banking financial studies and to serve as a reference for management and investors in making informed decisions. Keywords : Profitability, Solvency, Firm Value, Islamic Banks.